Analisis Interaksi Sosial dalam Pilihan Bahasa Komunikasi Etnis Mandailing dan Batak Toba - Natasya Kaila Putri; Nazlia Fahira; Frans Frans; Sri Sulastri Sitohang; Tri Indah Prasasti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The phenomenon of bilingualism and diglossia often occurs in societies that have more than one language, where individuals can choose a language based on the situation and the person they are talking to. This study aims to understand the perception of the use of regional languages by the Batak Toba and Mandailing ethnic groups in everyday communication. Qualitative methods were used with observation and interview techniques with students of the Geography Education Department at Medan State University. Based on the results of the study, it can be concluded that the Batak Toba ethnic group more often uses regional languages in communication with fellow ethnic groups, both on and off campus. Meanwhile, the Mandailing ethnic group shows flexibility in language use, with a tendency to use Indonesian more often, especially in the campus environment. Keywords: Batak Toba ethnicity, communication, Language choice, Mandailing ethnicity, sociolinguistics.